Unveiling the Link Between Low Testosterone and Worsening Heart Failure Symptoms: A Literature Review - Ryan Ardiansyah; Akhmad Sandy Sauqy (Talenta Publisher, 2025)
Background: Heart failure can result from a variety of factors, including hypertension, coronary artery disease, diabetes, obesity, smoking, and genetic predispositions. Research indicates that testosterone levels are markedly lower in patients with heart failure compared to healthy individuals, suggesting that low testosterone may play a role in the onset or progression of heart failure. Objective: This review endeavors to examine the impact of low testosterone levels on the clinical manifestations of heart failure patients. Methods: A literature review was conducted across three databases, Google Scholar, PubMed, and Science Direct, employing the keywords